STRATEGI PENETAPAN HARGA PRODUK GERABAH DALAM MENGHADAPI PERSAINGAN PASAR DI DESA BANYUMULEK KABUPATEN LOMBOK BARAT - Dewi Rispawati; Lale Puspita Kembang (Juremi: Jurnal Riset Ekonomi, 2026)
This study aims to analyze the pricing strategies of pottery products in facing market competition in Banyumulek Village, West Lombok Regency. The research is motivated by the increasingly fierce competition in the pottery craft industry, which requires artisans to implement appropriate pricing strategies to remain competitive and maintain the sustainability of their businesses. The study employed a qualitative approach with a descriptive approach. The informants included pottery artisans, pottery gallery owners, and others familiar with the development of the pottery industry in Banyumulek Village. Data collection techniques included observation, in-depth interviews, and documentation. Data analysis employed the interactive model of Miles, Huberman, and Saldaña, which encompasses data condensation, data presentation, and conclusion drawing. The results indicate that the pricing strategy for pottery products in Banyumulek Village takes into account the cost of raw materials, labor costs, manufacturing difficulty, product quality, product size, market demand, and competitors' prices. In addition to implementing competitive prices, artisans also offer discounts to customers who purchase large quantities and maintain product quality to enhance customer satisfaction. In facing market competition, artisans rely not only on pricing strategies but also on design innovation, product quality improvement, digital marketing expansion, and building strong customer relationships. These strategies have proven effective in increasing the competitiveness of Banyumulek pottery products and supporting the artisans' business sustainability amidst increasingly fierce market competition